2022
DOI: 10.3390/s22145242
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three 3D Segmentation Software Tools for Hip Surgical Planning

Abstract: In hip arthroplasty, preoperative planning is fundamental to reaching a successful surgery. Nowadays, several software tools for computed tomography (CT) image processing are available. However, research studies comparing segmentation tools for hip surgery planning for patients affected by osteoarthritic diseases or osteoporotic fractures are still lacking. The present work compares three different software from the geometric, dimensional, and usability perspectives to identify the best three-dimensional (3D) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 35 publications
(64 reference statements)
0
21
0
1
Order By: Relevance
“…Additionally, accurate and efficient tumor region segmentation methods are important to ensure the quality of quantitative image features. It has been confirmed that 3D Slicer has better segmentation algorithms and higher segmentation accuracy than other image segmentation software while being more accessible as free open-source software [ 42 ]. Moreover, the radiomics features extracted after image segmentation using 3D Slicer have higher robustness and are, therefore, recommended for use in high-throughput data mining efforts for medical oncology imaging [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, accurate and efficient tumor region segmentation methods are important to ensure the quality of quantitative image features. It has been confirmed that 3D Slicer has better segmentation algorithms and higher segmentation accuracy than other image segmentation software while being more accessible as free open-source software [ 42 ]. Moreover, the radiomics features extracted after image segmentation using 3D Slicer have higher robustness and are, therefore, recommended for use in high-throughput data mining efforts for medical oncology imaging [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to finally clarify this question, additional studies that specifically examine the HO, GO and LGHO between left- and right-handers are needed. The clinical consequence of these results are that, in contrast to the hip joint [ 26 , 27 ], for the surgical treatment of severe degenerative diseases or fractures in the shoulder joint, the healthy contralateral side cannot be used uncritically for planning the offset reconstruction. This hypothesis must be supported by further studies.…”
Section: Discussionmentioning
confidence: 99%
“…In our protocol, the CT scan of each specimen was segmented via a semi‐automated approach using the region growing function to produce individual masks of each bone, which were then output as 3D polygon models using the “Optimal” setting in the STL+ module in Mimics 11.11 or 19.0. Using the Mimics algorithms to produce 3D models has high geometrical accuracy even in areas such as the articulated hip joint, which is difficult to segment without significant manual editing of masks and has been shown to have dimensional accuracy of 0.353 mm (Mandolini et al, 2022). Although minor differences in minimum thresholding values among specimens were required to produce solid models (450–740 HU) in the current study, the bones examined were typically loose packed in the neutral position and therefore easily separated without consequential manual editing of masks.…”
Section: Methodsmentioning
confidence: 99%